2004
DOI: 10.1007/s00439-003-1071-9
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in PCSK9 causing autosomal-dominant hypercholesterolemia in a Utah pedigree

Abstract: Familial hypercholesterolemia results from mutations in the low-density lipoprotein (LDL) receptor or apolipoprotein B genes. We have previously reported the identification of a Utah autosomal-dominant hypercholesterolemia pedigree (kindred 1173) that did not show linkage to either of these loci (Hunt et al. 2000). Expansion of the pedigree and increased marker density within the region of interest have resulted in a multipoint LOD score of 9.6 and enabled us to decrease the size of the linked region to approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
187
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(194 citation statements)
references
References 11 publications
(15 reference statements)
1
187
0
6
Order By: Relevance
“…We did not observe an association (inverse or otherwise) of del12 with other known risk factors for coronary artery disease, such as hypertension, smoking status, obesity, or type 2 diabetes (Table S8 in Several studies have shown a strong positive correlation between the effects of lipid-associated sequence variants on non-HDL cholesterol levels and the risk of coronary artery disease. [7][8][9][10]29 However, in our data, several published variants deviated from the overall trend (Fig. 3, and Table S9 in the Supplementary Appendix).…”
Section: Coronary Risk and Del12mentioning
confidence: 47%
See 1 more Smart Citation
“…We did not observe an association (inverse or otherwise) of del12 with other known risk factors for coronary artery disease, such as hypertension, smoking status, obesity, or type 2 diabetes (Table S8 in Several studies have shown a strong positive correlation between the effects of lipid-associated sequence variants on non-HDL cholesterol levels and the risk of coronary artery disease. [7][8][9][10]29 However, in our data, several published variants deviated from the overall trend (Fig. 3, and Table S9 in the Supplementary Appendix).…”
Section: Coronary Risk and Del12mentioning
confidence: 47%
“…[5][6][7][8][9][10] In our search for new variants that affect non-HDL cholesterol levels, we applied a method 11 of interrogating whole genomes in samples obtained from a large number of Icelanders. We then tested for association between implicated variants and the risk of coronary artery disease.…”
mentioning
confidence: 99%
“…This suggestion was confirmed by the finding that missense mutations in PCSK9 are associated with an autosomal dominant form of hypercholesterolemia (10)(11)(12). The clinical phenotype of these subjects is indistinguishable from two other autosomal dominant forms of hypercholesterolemia, both of which are caused by defective receptor-mediated clearance of LDL: (i) familial hypercholesterolemia, which is caused by mutations in the LDLR; and (ii) familial defective apolipoprotein B (apoB), caused by mutations in the ligand for the LDLR (13).…”
mentioning
confidence: 76%
“…The third mutation, p.R218S, also in exon 4, was found in a French proband ascertained at age 45 with 402 mg/dl of total cholesterol and 293 mg/dl of LDL-C and presenting tendinous xanthoma and arcus corneae [Allard et al, 2005]. The p.D374Y mutation was reported in a hypercholesterolemic Utah kindred [Timms et al, 2004] and in three Norwegian families [Leren, 2004]. It was also found in three English families with 12 affected patients suffering from severe hypercholesterolemia, a family history of premature CHD, and requiring more stringent treatment than typical FH patients who are heterozygous for mutations in the LDL receptor gene [Sun et al, 2005].…”
Section: Biological Relevancementioning
confidence: 92%